Member heterogeneity in agricultural cooperatives: A systems-theoretic perspective - Constantine Iliopoulos; Vladislav Valentinov (Sustainability, 2018)
All over the globe, cooperatives are plagued by pervasive member heterogeneity problems that are induced by the radical and dynamic changes in the business environment. Most current solutions to these problems emphasize strengthening member loyalty and commitment. Yet, many of these solutions are symptomatic rather than fundamental. Searching for fundamental solutions, this paper draws on the Luhmannian system-environment paradigm. Bringing this paradigm to bear on the cooperative scholarship, the paper views cooperatives as operationally closed systems maintaining a precarious relationship to their outer environment, which includes cooperative members. In view of their operational closure, cooperatives tend to overstrain the carrying capacity of their environment by being active in the areas marked by a limited extent of the true commonness of member interests. This overstraining results in a host of problems associated with member heterogeneity. The fundamental solutions following from the system-environment paradigm require the adjustment of cooperative boundaries and goals in light of the evolving range of the true common interests of members. In terms of methodology, we review the extant literature, synthesize the main elements of the system-environment approach and conduct a meta-analysis of case studies and other empirical research to highlight our theoretical arguments.
Keywords: 330; cooperatives; sustainability; member heterogeneity; fundamental and symptomatic solutions; relative and absolute scarcity